2015
DOI: 10.1088/0004-637x/810/1/28
|View full text |Cite
|
Sign up to set email alerts
|

AN ELECTRON-TRACKING COMPTON TELESCOPE FOR A SURVEY OF THE DEEP UNIVERSE BY MeV GAMMA-RAYS

Abstract: Photon imaging for MeV gammas has serious difficulties due to huge backgrounds and unclearness in images, which are originated from incompleteness in determining the physical parameters of Compton scattering in detection, e.g., lack of the directional information of the recoil electrons. The recent major mission/instrument in the MeV band, Compton Gamma Ray Observatory/COMPTEL, which was Compton Camera (CC), detected mere ∼ 30 persistent sources. It is in stark contrast with ∼2000 sources in the GeV band. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 51 publications
2
69
0
Order By: Relevance
“…These measured results are consistent with the simulation results. Consequently, we found that the satellite-ETCC proposed in Tanimori et al (2015) would provide all-sky surveys of weak persistent sources of 13 mCrab with 10% polarization for a 10 7 s exposure and over 20 GRBs down to a 6 × 10 −6 erg cm −2 fluence and 10% polarization during a one-year observation. …”
mentioning
confidence: 87%
“…These measured results are consistent with the simulation results. Consequently, we found that the satellite-ETCC proposed in Tanimori et al (2015) would provide all-sky surveys of weak persistent sources of 13 mCrab with 10% polarization for a 10 7 s exposure and over 20 GRBs down to a 6 × 10 −6 erg cm −2 fluence and 10% polarization during a one-year observation. …”
mentioning
confidence: 87%
“…However, the astrophysics in the photon energy range 0.2-100 MeV is very rich, including GRBs, blazars, neutron stars, supernovae, etc; particularly the radioactive decay emissions from various sources. To study the spectacular astrophysics in the MeV gamma-ray range, a few missions and telescopes have been launched or proposed, for instance, the Satellite-ETCC (Electron-Tracking Compton Experiments, Tanimori et al 2015), the e-ASTROGAM space mission (Tatischeff et al 2016), and the AMEGO (All-sky Medium Energy Gamma-ray Observatory, Moiseev 2017; Rando 2017).…”
Section: Are the Gamma-ray Emissions Detectable?mentioning
confidence: 99%
“…A well-defined PSF is the most effective tool for background suppression similar to optical/X-ray telescopes, which suppresses for the most part of gamma rays coming from the outside of the PSF in particular major components, and it enables us to estimate the remaining contamination quantitatively. A particle identification using energy-loss rate (dE/dx) selects events in which the electron stopped in the gaseous volume [8]. The dE/dx rejects non-gamma-ray particles and electron-escaped events.…”
Section: Extragalactic Mev Gamma-ray Backgroundmentioning
confidence: 99%
“…Both SPI and HXD suffer from intense background radiations [2,6]. We have developed an electrontracking Compton camera (ETCC), which is the first MeV gamma-ray telescope to provide a welldefined point spread function (PSF) within a few degrees and efficient background rejection [7,8].We note the PSF is defined with two directional angles similar to optics, whereas in standard Compton cameras, the angular resolution is defined with only one directional angle. We have revealed a satellite equipped with four modules of (50 cm) 3 -sized ETCCs, that will reach a sensitivity of 1 mCrab [8].…”
Section: Introductionmentioning
confidence: 99%